Market segmentation: the gay consumer profile (Research, Society and Development, 2019)
This article aims to identify consumer behavior within the gay market segment, analyze the underlying consumption habits, and understand consumer sentiment about the corporate messages directed to this market segment. Supporting this research was an online questionnaire of 43 questions relating to consumer focusing on three axes: 1) demographics, 2) consumption habits, and 3) motivations and influences before and after the purchase of products. The majority of respondents were highly educated, and almost a fifth (19.52%) of them were in a stable relationship. All respondents reacted negatively to perceived brand attempts to target "pink money”. With respect to marketing campaigns, no respondents felt that companies were obliged to include or treat the gay community differently. In fact, they indicate that marketers should develop natural, inclusive messaging campaigns that avoid differentiating the gay consumer segment from their heterosexual peers.